1991
DOI: 10.1159/000293106
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Clinical Signs and Hypercoagulable State in Toxemia of Pregnancy

Abstract: The hypercoagulable state in patients with toxemia of pregnancy was investigated in comparison with normal pregnant women using new coagulation parameters, mainly thrombin-antithrombin III (TAT) complexes, Α2-antiplasmin-plasmin complexes (PIP), and D-dimer FDP. When the patients were categorized by the classification of the WHO Study Group (1985), significant increases of TAT complexes and Α2-PIP complexes with decreases of the ATIII level were observed in the groups with preeclampsia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 28 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…Normal pregnancy is characterized by an increased plasma concentration of protein Z [37], which has been proposed to be part of a compensatory mechanism for the increased concentration of factor X [37] and perhaps for the increased thrombin generation. Preeclampsia is associated with an exaggerated hypercoagulable state and excessive thrombin generation [1,25,38], as determined by higher maternal plasma concentrations of TAT complexes [25][26][27][28]39,40] and lower antithrombin III concentrations [41][42][43][44][45] than patients with normal pregnancies. Moreover, patients with PE who deliver preterm have a higher rate of thrombotic lesions in the decidua [9,20] and in the placental villi [23] than normotensive patients with indicated or spontaneous preterm delivery [20,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal pregnancy is characterized by an increased plasma concentration of protein Z [37], which has been proposed to be part of a compensatory mechanism for the increased concentration of factor X [37] and perhaps for the increased thrombin generation. Preeclampsia is associated with an exaggerated hypercoagulable state and excessive thrombin generation [1,25,38], as determined by higher maternal plasma concentrations of TAT complexes [25][26][27][28]39,40] and lower antithrombin III concentrations [41][42][43][44][45] than patients with normal pregnancies. Moreover, patients with PE who deliver preterm have a higher rate of thrombotic lesions in the decidua [9,20] and in the placental villi [23] than normotensive patients with indicated or spontaneous preterm delivery [20,23].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis has been proposed as a mechanism of disease in preeclampsia (PE) [9][10][11][12][13], intrauterine growth restriction (IUGR) [13][14][15][16][17], stillbirth [18], recurrent pregnancy losses [19], and preterm delivery [20][21][22]. Evidence in support of this view includes: (1) an excessive rate of thrombotic lesions in the placental villi [23] and decidual vessels [20,23,24] in patients with these pregnancy complications, and (2) higher maternal plasma concentrations of thrombin-anti-thrombin (TAT) complexes in patients with PE [25][26][27][28] and small for gestational age (SGA) neonates [25].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, inhibition of platelet aggregation by prostacyclin-like activity [3], inhibition of blood coagulation by thrombomodulin [4] and fibrinolysis by tissue plasminogen activator [5] play important roles in the regulation of blood coagulation in the placenta. It is known that coagulation abnormalities are present in preeclampsia [6]. Enhanced thrombin formation and endothelial damage are reported in patients with preeclampsia [7].…”
Section: Introductionmentioning
confidence: 99%
“…Terao et al [10] found a strong correlation between clinical parameters of preeclampsia and coagula tion activities. We also found an exaggerated form of coagulation and fibrinolytic activities in all the patients.…”
Section: Discussionmentioning
confidence: 98%
“…For correlation analysis, we calculated the clinical index (for edema, pro teinuria and systolic blood pressure) and coagulation index A (for AT III antigen, PIC and D dimer) as described by Terao et al [10]. We also did a canonical correlation analysis among the most important clinical parameters: level of consciousness at the time of admission, 98 Halim/Bhuiyan/Azim/Khatun/Kanayama/ Blood Coagulation and Fibrinolysis in El Maradny/Maehara/Hiroshi/Terao Eclamptic Patients Table 4.…”
Section: Statistical Analysis and Canonical Correlation Analysismentioning
confidence: 99%